SENGKETA TANAH EKS KERAJAAN DI KOTAWARINGIN BARAT PROVINSI KALIMANTAN TENGAH - I Gusti Ayu Gangga Santi Dewi (Faculty of Law, Universitas Diponegoro, 2019)
Conflicts that ended in court disputes often occurred in the former Kotaringin Kingdom related to the former kingdom lands. Phenomenon of substantive injustice related to former kingdom land policy in the Dictum Fourth letter A UUPA which abolishes former kingdom land and shifts to the State, is an injustice felt by former kingdom parties. Research with the Socio Legal approach with social science methods and theories about law. This research was focused on looking at the facts of the conflict that ended in court disputes and the solution to prevent the disputes of former kingdom land in Kotawaringin Barat.